Pengembangan E-Modul Model Flipped Classroom Pada Pembelajaran Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa Sekolah Dasar - Danuri, Danuri; Nurjanah, Eka (Universitas Muhammadiyah Magelang, 2022)
The purpose of this study was to find out the process of developing teaching materials for the E-Module Mathematics and to find out the increase in students' mathematical reasoning abilities using the E-Module Mathematics. This type of research is research and development of the Borg and Gall model. A total of 21 fifth grade students became subjects in this study. Data collection techniques in the form of test guidelines, interviews, and questionnaires. The data analysis technique used is descriptive statistics in the form of assessments from material experts and media experts, assessment of teacher responses and student responses, validity tests, reliability tests, normality tests, and inferential statistics, namely the T-test. The contribution of this paper is to describe the process of developing appropriate and effective teaching materials to improve the mathematical reasoning abilities of elementary school students. The results of the study are as follows: 1) the teaching materials for the Mathematics E-Module are developed from gathering information to field tests, 2) the teaching materials developed are declared fit for use with good criteria, indicated by the material expert's assessment with a percentage score of 78% and the media expert's assessment with percentage score of 82%. 3) Mathematics E-Module teaching materials are effectively used in learning, as indicated by the results of the calculation of the Paired Sample T-test obtained a significance value (2-tailed) of 0.000 (p <0.05), 4) Students' mathematical reasoning abilities increased as indicated by the average acquisition -the average pretest score is 66.95 and the average posttest score after using teaching materials is 81.57.